Review of Portuguese Cistercian Monastic Heritage - Martins, Ana Maria Tavares (2020)
This paper aims to present a contribution to the history of the reform and renewal in the Portuguese Cistercian monasteries throughout almost nine centuries of cultural and architectural history in this Country but focusing on the Beira’s Region. The Cistercian Order played a remarkable role in the affirmation of Portugal (1143) and had unquestionable position, since the medieval period, in the construction of a significant part of the Portuguese culture. The reform of many Monasteries came with the Autonomous Congregation of Alcobaça (1567). In fact, the Portuguese Cistercian Monasteries absorbed the regional ways of construction with masonry (granite in the north and limestone in the south) but it is without a doubt in its architecture that change and renewal can be found as strength and a tool for achieving a status of cultural landmarks. The renewal and reform in the Portuguese Cistercian Monasteries was not restricted to the styles in vogue but also was related to the physical expansion of the monasteries. This could be achieved by adding new aisles and cloisters like in Alcobaça or Salzedas Monasteries. Though there are cases of unconventional renewals and reformations such as the existence of two churches in the Monastery of Salzedas and the example of the open air Museum of the Monastery of S. João de Tarouca were can be found the former medieval monastery, as a result of new archaeological research and a prospective hypothesis of its volumetric layout, in between the walls of the 17th century dormitories and the Church. This continuous architectonic renewal is still being carried out in the 21st century either by the Portuguese Government through several heritage institutes since the 20th century or a few individuals on their one.The history of the Portuguese Cistercian Monasteries blends itself with the history of Portugal as the continuous architectonic renewals and reforms were also a result of nine centuries of events and changes in this Country.